2022
DOI: 10.3390/pr10010101
|View full text |Cite
|
Sign up to set email alerts
|

Nitinol Type Alloys General Characteristics and Applications in Endodontics

Abstract: A very extensive literature review presents the possibilities and needs of using, in endodontics, the alloys commonly known as nitinol. Nitinol, as the most modern group of engineering materials used to develop root canals, is equilibrium nickel and titanium alloys in terms of the elements’ atomic concentration, or very similar. The main audience of this paper is engineers, tool designers and manufacturers, PhD students, and students of materials and manufacturing engineering but this article can also certainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 468 publications
0
9
0
Order By: Relevance
“…Endodontic therapy entails removing contaminated tissue from a tooth’s root canal system, contouring and disinfecting the canals, and refilling the canals with the appropriate ingredients. In endodontics, using rotary files ( Figure 16 ) made of nickel-titanium (NiTi) has revolutionized root canal treatment ( Dobrzański et al., 2022 ).
Figure 16 Endodontic application of Rotary file ( Philip et al., 2017 ).
…”
Section: Applications Of Ti and Ti Alloys In Dentistrymentioning
confidence: 99%
“…Endodontic therapy entails removing contaminated tissue from a tooth’s root canal system, contouring and disinfecting the canals, and refilling the canals with the appropriate ingredients. In endodontics, using rotary files ( Figure 16 ) made of nickel-titanium (NiTi) has revolutionized root canal treatment ( Dobrzański et al., 2022 ).
Figure 16 Endodontic application of Rotary file ( Philip et al., 2017 ).
…”
Section: Applications Of Ti and Ti Alloys In Dentistrymentioning
confidence: 99%
“…Experimental evidence does not support the use of these gels, as they not only do not reduce the friction between the instrument and the dentinal canal, but in some cases even increase it [13]. Aqueous solutions (or even distilled water) are much more useful, as they wash the dentinal detritus from the grooves of the instruments more efficiently [9,13]. The use of NaOCl solution during instrumentation is standard because in addition to acting on bacteria and dissolving tissue debris, it is also very effective as a lubricant.…”
Section: Discussionmentioning
confidence: 98%
“…However, beneath this thin layer of titanium oxide (which also contains small amounts of nickel) is a nickel-rich sublayer that is responsible for corrosion [11]. It is believed that this surface oxide film of titanium oxide increases the stability of the surface layers of the alloy, protects against corrosion and ensures the stability of the material itself [13]. According to the results of research by Stokes and associates who examined the corrosive effect of new, unused Ni-Ti instruments from five different manufacturers, it was confirmed that the occurrence of corrosion on new instruments is influenced by the instrument production process, ie the quality of control of the manufacturing process [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu-based shape memory alloys (SMAs) exhibit remarkable properties, such as super elasticity and shape memory effect, attributed to a diffusionless reversible martensitic transformation [1][2][3]. Due to their affordability and ease of processing, Cu SMAs are utilized in various fields, including medicine, electronics and aerospace [4][5][6][7]. Among these alloys, copper-aluminum-based alloys (Cu-Al) are characterized by their exceptional mechanical properties, excellent electrical and thermal conductivity, and relatively low cost compared to other SMAs, such as Ni-Ti alloys [4,7].…”
Section: Introductionmentioning
confidence: 99%